PEMBUATAN APLIKASI GAME EDUKASI ANAK-ANAK TENTANG SEJARAH ISLAM MENGGUNAKAN CONSTRUCT 2 BERBASIS ANDROID - Mohamad Iqbal Hargani Fajri; Yolen Perdana Sari (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Create an online game with the title Children's Educational Game About Islamic History using the Construct 2 application so that it can provide alternative entertainment for people who like online game entertainment. How to make an educational game application about Islamic history to make it easier for children to recognize Islamic history.Reduce parents' anxiety about children when playing games. The qualitative method is a method of researching an object, a group of people, a method that raises problems by collecting data. given to describe the characteristics of a situation or object of a study and draw a conclusion that will be carried out. The source of the data in the research is a very important factor, because the source of the data will concern the quality of the results of a study. With the Making of an Educational Game Application for Children About Islamic History Using Construct 2 Based on Android, it can increase students' interest in learning, because the packaging of the game is made as attractive as possible. and not boring. In the further development of this application, it is hoped that this application will not only display quizzes for students of SDN Kepuhuhan 01, but for every level of study. Especially if it is developed for each existing subject. In further development of this application, it is hoped that this application can not only run on one platform, namely Android.